Physiological, Nutritional and Performance Profiles of Brazilian Jiu-Jitsu Athletes - Andreato L.V.* (2016)
© Editorial Committee of Journal of Human Kinetics 2016.This study analysed the physiological, nutritional and performance profiles of athletes practicing Brazilian jiu-jitsu. To this end, 15 athletes that practiced Brazilian jiu-jitsu (aged: 28 ± 5 years; 8 brown belts and 7 black belts; training experience: 11 ± 4 years) underwent anthropometric measurements (body composition and somatotype), dietary evaluation (24 h recall) and physical fitness tests (movement time, dynamometer handgrip, kimono grip strength, vertical jump and sit-and-reach tests). The athletes had 12.7 ± 4.8% of body fat, 59.2 ± 5.0% of muscle mass and their somatotype was dominated by the mesomorphic component (5.3 ± 2.0), followed by endomorphic (3.7 ± 1.5) and ectomorphic (1.4 ± 0.9) components. Nutritional assessment suggested a diet consisting of 54 ± 7% of carbohydrates, 19 ± 4% of protein and 27 ± 6% of lipids. Movement time on the handgrip tests was 0.42 ± 0.05 s, for handgrip strength, 53 ± 7 kgf was found for the dominant hand and 50 ± 9 kgf for the non-dominant hand. For the countermovement jump, the jiu-jitsu athletes reached 41 ± 5 cm. Athletes remained 30 ± 14 s in the maximum static suspension test gripping a kimono, and reached 27 ± 8 cm in the sit-and-reach test. Overall the sample presented average levels of body fat, elevated muscle mass and a predominantly mesomorphic somatotype. Diet was generally poor, with low carbohydrate intake, high protein intake and adequate lipid intake. Maximum isometric handgrip strength was consistent with observations of other athletes in this sport discipline. However, the performance in the maximum static suspension test gripping a kimono was lower than in other Brazilian jiu-jitsu athletes. Movement time was comparable and lower body muscle power was worse compared to athletes in similar sports. Additionally, flexibility was rated as poor.